2005
DOI: 10.1179/crn.2005.019
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Systemic Joint Hypermobility and Temporomandibular Joint Hypermobility in Pregnancy

Abstract: The purpose of this study was to establish a possible correlation between systemic hypermobility and temporomandibular hypermobility during pregnancy. One hundred (100) healthy pregnant women were evaluated: 7% in the first trimester (1T), 38% in the second trimester (2T), and 55% in the third trimester (3T) of gestation. In the series, the authors analyzed systemic joint hypermobility (SJH), range of mandibular movement (MMR), head and shoulder posture, head lateralization, and the presence of noise, pain, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
0
12
0
2
Order By: Relevance
“…The GJH was assessed by the Carter and Wilkinson's criteria, modified by Beighton 29 , which have been used in numerous studies 4,6,[11][12][13][14][15][16] about hypermobility. Beighton's score assesses 9 joints by means of 5 tests: passive thumb opposition to the anterior portion of the forearm, until they touch; passive dorsiflexion of the little finger until it comes parallel to the forearm; elbow and knee hyperextension higher than 10 degrees; trunk flexion with the knees completely extended, in such a way that the palms of the hands touch the floor (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GJH was assessed by the Carter and Wilkinson's criteria, modified by Beighton 29 , which have been used in numerous studies 4,6,[11][12][13][14][15][16] about hypermobility. Beighton's score assesses 9 joints by means of 5 tests: passive thumb opposition to the anterior portion of the forearm, until they touch; passive dorsiflexion of the little finger until it comes parallel to the forearm; elbow and knee hyperextension higher than 10 degrees; trunk flexion with the knees completely extended, in such a way that the palms of the hands touch the floor (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…There are reports that this syndrome is more prevalent in women and in individuals of Asian and African descent, and it reduces with aging 8,9 . GJH has been associated with the development of signs and symptoms of TMD [4][5][6][10][11][12][13][14][15][16] . It is known that although the TMJ is among hypermobile joints, it may predispose some patients to subluxation, although not necessarily with pain or dysfunction 4 .…”
Section: Introductionmentioning
confidence: 99%
“…contrary, Charlton et al (20) found that high serum estrodiol levels during the third trimester of pregnancy correlated with increased laxity of anterior cruciate ligament by measuring anterior tibial translation. And Silviera et al (21) observed a high incidence of systemic hypermobility which was not correlated with mandibular hypermobility and TMD in pregnancy. In the present study, the prevalence of systemic joint hypermobility was found to be not different between the pregnant and non-pregnant women.…”
Section: Discussionmentioning
confidence: 97%
“…With similar objective, a study evaluating 70 pregnant women 14 has not found higher prevalence of systemic joint hypermobility as compared to non-pregnant women. In addition, and similar to the already mentioned study 13 , it was not possible to establish association between systemic joint hypermobility and TMJ hypermobility. If estradiol and progesterone levels influence orofacial pain experience, a decrease in pain reports may be expected during pregnancy.…”
Section: Contentsmentioning
confidence: 89%
“…Reported pain rates, which decreased throughout pregnancy, have returned to baseline values in one year after delivery. The same was true to estradiol 13 has studied the possible association of systemic joint hypermobility and temporomandibular joint hypermobility in pregnant women as a way to establish a higher predisposition to the development of TMD. Although not finding an association between both conditions, there has been a prevalence of 46% TMJ hypermobility during mouth opening among pregnant women.…”
Section: Contentsmentioning
confidence: 99%